-x²+5x+14=0 | · (-1)
x²-5x-14=0
D=(-5)²-4·(-14)=25+56=81=9²
D>0 => уравнение имеет два корня
x1=(5-9)/2=-4/2=-2
x2=(5+9)/2=14/2=7
ответ: x1=-2; x2=7.
x²+x-20=0
D=1²-4·(-20)=1+80=81=9²
x1=(-1-9)/2=-10/2=-5
x2=(-1+9)/2=8/2=4
ответ: x1=-5; x2=4.
-x²+5x+14=0 | · (-1)
x²-5x-14=0
D=(-5)²-4·(-14)=25+56=81=9²
D>0 => уравнение имеет два корня
x1=(5-9)/2=-4/2=-2
x2=(5+9)/2=14/2=7
ответ: x1=-2; x2=7.
x²+x-20=0
D=1²-4·(-20)=1+80=81=9²
D>0 => уравнение имеет два корня
x1=(-1-9)/2=-10/2=-5
x2=(-1+9)/2=8/2=4
ответ: x1=-5; x2=4.